Transboundary capital and pollution flows and the emergence of regional inequalities - Simon Levin; Anastasios Xepapadeas (Fondazione Eni Enrico Mattei (FEEM), 2015)
We seek to explain the emergence of spatial heterogeneity regarding development and pollution on the basis of interactions associated with the movement of capital and polluting activities from one economy to another. We use a simple dynamical model describing capital accumulation along the lines of a fixed-savings-ratio Solow-type model capable of producing endogenous growth and convergence behavior, and pollution accumulation in each country with pollution diffusion between countries or regions. The basic mechanism underlying the movements of capital across space is the quest for locations where the marginal productivity of capital is relatively higher than the productivity at the location of origin. The notion that capital moves to locations of relatively higher productivity but not necessarily from locations of high concentration to locations of low concentration, does not face difficulties associated with the Lucas paradox. We show that, for a wide range of capital and pollution rates of flow, spatial heterogeneity emerges even between two economies with identical fundamental structures. These results can be interpreted as suggesting that the neoclassical convergence hypothesis might not hold under differential rates of flow of capital and polluting activities among countries of the same fundamental structure.
Keywords: O44; R12; Q52; C65; 330; Transboundary Flows; Capital; Pollution; Diffusion; Turing Instability; Spatial Heterogeneity